Implikasi Hukum Terhadap Perkawinan Anak: Pelanggaran Hak-Hak Anak dan Tanggung Jawab Negara - Andi Laila Qadrianti Putri; Annisa Febyanti; Bilqisti Kurrotul Aini; Bagus Sugara Putra; Nurul Amaliyah Putri (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
In general, the purpose of marriage is to fulfill human desires in order to create a happy household, in accordance with applicable regulations. However, today the marriage of minors has become an increasingly pointed issue in the context of law, humanity and the protection of human rights. Child marriages often involve one party who has not reached the age of majority, causing a wide and serious impact on the rights of children and society in general. This paper aims to examine more deeply how Indonesian law regulates the age limit of marriage and whether these rules are effective in preventing child marriage, as well as to describe the legal impact of child marriage and the role of the government in strengthening legal protection for victims of child marriage. The method used in this paper is a normative legal writing method using data collection techniques through document study activities on secondary data. The findings of this paper are that children involved in marriage often lack the ability to give free consent. In many cases, child marriage violates the fundamental rights of children in accordance with the UN Convention on the Rights of the Child, Indonesian positive law and other international laws that protect children from exploitation, violence and discrimination. The state's responsibility is not only limited to enforcing laws and regulations that protect children from exploitation, violence and discrimination.